2020
DOI: 10.1021/acs.jpclett.0c01177
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Noncovalently Functionalized Boron Nitride Nanotubes with High Stability and Water-Redispersibility

Abstract: Boron nitride nanotubes (BNNTs) have attracted significant interest because of the remarkable difference in their physical properties compared with carbon nanotubes and their far-reaching potential applications, including electrical insulators; thermally conducting, catalytic, and piezoelectric materials; and neutron absorbers. Despite their unique physical properties, the bundling and insolubility of BNNTs in water because of its substantial van der Waals attraction and hydrophobicity, respectively, give rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
(32 reference statements)
1
17
0
Order By: Relevance
“…Structural characterizations of surfactant-dispersed BNNTs using HRTEM have not been investigated in detail (Table S1). 40,41 Figure 3c presents a typical HRTEM image of individual BNNTs, whose outer walls are clean and crystalline. The direct TEM imaging shows the possibility that the surfactant-dispersed BNNTs can be used for building 1D heteronanotubes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural characterizations of surfactant-dispersed BNNTs using HRTEM have not been investigated in detail (Table S1). 40,41 Figure 3c presents a typical HRTEM image of individual BNNTs, whose outer walls are clean and crystalline. The direct TEM imaging shows the possibility that the surfactant-dispersed BNNTs can be used for building 1D heteronanotubes.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome these issues, we turned our attention to surfactant-dispersion techniques, which have been extensively developed for the isolation of CNTs. , As opposed to covalent functionalization, surfactant wrapping employs noncovalent functionalization, which causes little damage to BNNTs. Surfactant-assisted dispersion of BNNTs has been developed so far; , however, no literature has focused on the morphology of the prepared BNNT networks. In particular, the dispersibility and surface cleanliness of the suspended BNNTs, which are key factors for the coaxial growth of heteronanotubes, still remain elusive.…”
mentioning
confidence: 99%
“…This might be due to a signicant reduction in the maximum possibility of collisions and directional deections of phonon within the nanoparticles; therefore, the reduced phonon scattering and interfacial thermal resistance during heat conduction lead to higher conductivity and the formation of several heat conduction paths, 224 as displayed in Fig. 24( 225 They synthesized BNNTs successfully via an induction thermal plasma method. 226 Synthesized BNNT powder (0.1 wt%) was dispersed in water along with a cationic surfactant solution of 0.5 wt% cetyltrimethylammonium 4-vinylbenzoate.…”
Section: Non-covalent Functionalization Of H-bnmentioning
confidence: 99%
“…Recently, Kang et al reported an interesting work on the synthesis of non-covalently functionalized BNNSs with significant stability in water and redispersibility. 225 They synthesized BNNTs successfully via an induction thermal plasma method. 226 Synthesized BNNT powder (0.1 wt%) was dispersed in water along with a cationic surfactant solution of 0.5 wt% cetyltrimethylammonium 4-vinylbenzoate.…”
Section: Functionalization Of H-bnmentioning
confidence: 99%
“…Various methods have been developed for achieving stable dispersions of BNNTs in aqueous solutions. For example, covalent functionalization through acid treatment, , wet chemistry methods, chemical vapor deposition, and noncovalent functionalization using amphiphilic molecules such as surfactants and polymers are well-known and widely applied methods. Covalent (chemical) functionalization through acid treatment or wet chemistry has been reported to improve the stability and dispersibility of BNNTs in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%